Foreign Capital in the Chinese Stock Market: A Firm-Level Study - Lundblad, Christian T.; Shi, Donghui; Zhang, Xiaoyan; Zhang, Zijian (Journal of Financial and Quantitative Analysis, 2026)
Abstract Using a proprietary data set covering all foreign investors’ daily trades in the Chinese stock market from 2016 to 2019, we find that foreign order flows, facilitated by regulatory liberalization through several channels, present strong predictive power for future stock returns, implying that these order flows are likely informed. We track the source of this informativeness and find that foreign order flows significantly predict firm-level news and news-day returns, suggesting that foreign investors can effectively process local firm information. Finally, we find that regulatory reforms that generally relax investment access requirements further improve foreign investors’ predictive power.